Allitol: production, properties and applications. (17th November 2016) - Hassanin, Hinawi A. M.; Mu, Wanmeng; Koko, Marwa Y. F.; Zhang, Tao; Masamba, Kingsley; Jiang, Bo
Summary: Allitol is a rare alcohol monosaccharide sweetener containing six carbons atoms. It is a major product of thed ‐psicose reduction pathway that exerts various physiological effects, for example laxative effects for the treatment of constipation and anti‐obesity effects by suppressing lipid accumulation. Allitol can be also used as an anticrystallisation agent. In addition, allitol cross‐linksd ‐ andl ‐hexoses, thus contributing to production ofl ‐psicose. This is a review of the recent studies on the sources, properties, physiological functions and applications of allitol. In addition, the biochemical properties of ribitol dehydrogenase enzymes and the biotechnological production of allitol via microbial and enzymatic synthesis fromd ‐psicose and directly fromd ‐fructose are reviewed. Abstract : Rare sugars applications.